Phytochemical analysis, antioxidant and anti-inflammatory activities of Phyllanthus simplex - Chouhan H.S.; Singh S.K. (My University, 2025)
Ethnopharmacological relevance: Phyllanthus simplex (Family: Euphorbiacae) is widely used in traditional medicines for treatment of various diseases including inflammation. Materials and methods: Petroleum ether extract (PSPE) and ethanol extract (PSEE) of the whole plant of Phyllanthus simplex were characterized for their total phenolics, tannins and flavonoids content. These extracts were standardized by HPTLC using phyllanthin and gallic acid respectively as markers. Antioxidant activity of extracts was evaluated by the DPPH, hydroxyl and superoxide radicals scavenging assay. The total antioxidant capacity of extracts was determined. Anti-inflammatory activity was evaluated by their effect on nitric oxide (NO) production in isolated rat peritoneal macrophages; carragennan-induced paw edema and formation of cotton pellet-induced granuloma in rats. Results: Abundance of phenolics was found in PSEE. Phyllanthin and gallic acid content in PSPE and PSEE were found to be 14.5 and 0.65% (w/w) respectively. PSEE showed concentration dependent significant scavenging of DPPH, hydroxyl and superoxide radicals with IC 50 values 102.219, 171.485 and 24.73 μg/ml respectively. PSEE significantly inhibited NO production in isolated rat peritoneum macrophages. Moreover, it also exhibited significant inhibition of carragennan-induced paw edema (58.48 ± 0.028%, p < 0.001, at 6 h, 200 mg/kg oral dose) and cotton pellet-induced granuloma formation (45.671 ± 0.712%, p < 0.001, at 200 mg/kg oral dose). Anti-inflammatory activity of PSEE was found to be comparable to diclofenac sodium. Conclusions: Significant antioxidant and anti-inflammatory activities were found in PSEE which may be attributed to its high phenolic content. © 2011 Elsevier Ireland Ltd. All rights reserved.